Data governance activities: a comparison between scientific and practice-oriented literature. Issue 2 (5th March 2018) - Alhassan, Ibrahim; Sammon, David; Daly, Mary
Abstract : Purpose: The purpose of this paper is to explore the current literature on data governance in scientific and practice-oriented publications, and to provide a comparative analysis of the activities reported for data governance. Data have become a key organisational asset and data governance both a necessary and critical activity. Design/methodology/approach: A comprehensive literature review is conducted in order to identify the published material that reflects the current state of knowledge. A systematic procedure was followed that identified 61 publications that explicitly mention data governance activities. Open coding techniques were applied to conduct content analysis, resulting in the identification of 591 concepts. A critical analysis also identified gaps in the literature. Findings: The analysis identified 120 data governance activities which are understood as: "action" plus "area of governance" plus "decision domain" (e.g. define data policies for data quality). The authors define and present a data governance activities model based on the analysis. The analysis also shows a higher volume of data governance activities reported by practice-oriented publications that are associated with the "implement" and "monitor" actions of the areas of governance across the decision domains compared with scientific publications, whereas The authors found that the scientific publications focus more on defining activities. The results contribute to identifying research gaps and concerns on which ongoing and future research efforts can be focused. Research limitations/implications: This paper is of interest to both academics and practitioners, as it helps them understand the activities associated with a data governance programme. Current literature fails to provide a comprehensive understanding of the data governance activities that are required when considering a data governance programme. Therefore, the proposed model for data governance activities can be used to give insights into these activities. Originality/value: To the knowledge of the authors, this study is the first to explicitly consider data governance activities from both an academic and practice-oriented perspective.